Student Development through Comprehensive Training for Placement Improvement: A Quality Circle Approach - A., Sujil; Metri, R. A.; Patil, V. B.; Pandey, A. S.; Patil, S. S.; Kalkhambkar, V. N. (Journal of Engineering Education Transformations, 2025)
Contribution of Engineering Education to the sustainable development of the industry have shown its importance. In each phase of industry revolution, core engineering branches have played significant role by providing competent engineering graduates. Over the years’ industry requirements are changed accordingly the employability skills of the graduates needs to be uphold. Further, the core engineering branches are facing challenges to adopt the revolution of allied engineering branches and courses. To address these issues, the students of core engineering branches to be trained in various dimensions for filling this gap. Thus, the paper discusses the development of students of core engineering through means of comprehensive training to make them employable with quality circle approach. The comprehensive training has been conducted for specific set of students of electrical engineering for placements in core companies with higher packages. Various surveys have been conducted to identify the skill-set requirements of students and expectations of industry. Accordingly, the comprehensive trainings were organized by considering the feedback from the survey conducted. The outcome of the comprehensive training is found to be efficient in terms of placement opportunities and improvements in packages.